1997
DOI: 10.1108/09534819710175839
|View full text |Cite
|
Sign up to set email alerts
|

The functions of methods of change in management consulting

Abstract: States that highly structured methods and tools for bringing about organizational change are frequent features in both the management literature and the practice of management consultants. Reports that, in order to understand the nature and popularity of these methods and tools, a study of the availability and use of methods in business process re‐engineering (BPR) projects was carried out in five large consulting companies. Identifies six functions of methods on the basis of this study. Finds that methods pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 8 publications
(5 reference statements)
0
90
0
1
Order By: Relevance
“…An evaluation of five leading management consulting companies in Sweden found that a clear structured working method was important for the internal work in the consulting company, the internal work in the client company, and the cooperation between them [33]. Besides, a clear work structure increased the competence in the consulting company and acted as a competence bank and contained more knowledge and experience than an individual consultant could manage [33].…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of five leading management consulting companies in Sweden found that a clear structured working method was important for the internal work in the consulting company, the internal work in the client company, and the cooperation between them [33]. Besides, a clear work structure increased the competence in the consulting company and acted as a competence bank and contained more knowledge and experience than an individual consultant could manage [33].…”
Section: Discussionmentioning
confidence: 99%
“…By the turn of the millennium, BPR became a familiar issue for strategy consulting firms and hence evolved into a hybrid or exploitative practice. This development is supported by a study regarding established strategy consulting firms indicating the use of 'strikingly similar' methods and tools for business process re-engineering (Werr et al, 1997). ICT-based knowledge management has enabled the development of exploitative consulting practices, the commodification of knowledge and attracted new entrants.…”
Section: Offered By Increasingly Large Numbers Of Competent Firmsmentioning
confidence: 87%
“…Proposition 1 follows directly from the TPS DNA established by Spear and Bowen (1999) which is readily understood via the Werr et al (1997) four level prism model. Corollary 1 is hinted at via the inventory analysis by Chen et al (2005), and confirmed via the QSAM audits by Childerhouse (2002).…”
Section: Handling Capabilitymentioning
confidence: 93%
“…The output from the Spear and Bowen (1999) research is best illustrated using the concept of the prism model conceived by Werr et al (1997). This requires the 'vision', 'principles', 'toolbox' and 'learning organizations' characteristics of any methodology to be clearly identified.…”
Section: The Prism Model Of Tpsmentioning
confidence: 99%
See 1 more Smart Citation